Habitat heterogeneity drives fern species diversity in Bilar, Bohol, Philippines using Hill numbers - MA. ANELI A. LANZADERAS; MERI JOYCE SALDOM; ANGELICA P. BALDOS (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Lanzaderas MAA, Saldom MJ, Baldos AP. 2026. Habitat heterogeneity drives fern species diversity in Bilar, Bohol, Philippines using Hill numbers. Biodiversitas 27 (2): d270237. https://doi.org/10.13057/biodiv/d270237. Ferns are ecologically vital components of tropical ecosystems, yet remain underrepresented in biodiversity assessments. This study applied the Hill numbers framework to evaluate the α-diversity of ferns across four habitat types: forest area, hilly terrain, open area, and riparian zone in Bilar, Bohol, Philippines. A total of 24 plots (10 m x 10 m each) were established, with three quadrats per habitat type in each barangay, covering an aggregate area of 2,400 m2. From these plots, we recorded 2,033 individual ferns representing 19 species. Species richness (q = 0) was highest in hilly terrain (13 species), followed by forest area (10), riparian zone (10), and open area (6). At q = 1 and q = 2, the effective numbers of species indicated comparable diversity between hilly terrain, forest area, and riparian zone, while open area showed significantly lower evenness and dominance (p<0.05). Nephrolepis cordifolia and Christella acuminata were the most widespread and abundant taxa, whereas Diplazium esculentum occurred exclusively in riparian zone, underscoring microhabitat specificity. The application of Hill numbers provided a more comprehensive and scale-independent understanding of fern diversity than traditional indices, capturing differences in both species richness and evenness. These findings emphasize that structurally and topographically complex habitats sustain higher effective species numbers. The study advocates prioritizing heterogeneous landscapes in conservation and restoration programs to enhance ecological resilience and safeguard fern diversity in fragmented tropical forests.